501 most notorious crimes - Donnelley, Paul (London Bounty Books, 2013)
In 501 Most Notorious Crimes, the reader will find a fascinating line-up of notorious crooks, criminals, villains and thieves, from the mysterious disappearance of Lord Lucan, the assassination of JFK to the treason committed by Guy Fawkes. This book provides a fascinating insight into the world's most notorious crimes.
Includes index.
First published in Great Britain in 2009 by Bounty Books, a division of Octopus Publishing Group Limited.
Keywords: Crime -- History; Criminals -- History; Crime